If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(8x + -1) = -3(x + -1) Reorder the terms: 4(-1 + 8x) = -3(x + -1) (-1 * 4 + 8x * 4) = -3(x + -1) (-4 + 32x) = -3(x + -1) Reorder the terms: -4 + 32x = -3(-1 + x) -4 + 32x = (-1 * -3 + x * -3) -4 + 32x = (3 + -3x) Solving -4 + 32x = 3 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -4 + 32x + 3x = 3 + -3x + 3x Combine like terms: 32x + 3x = 35x -4 + 35x = 3 + -3x + 3x Combine like terms: -3x + 3x = 0 -4 + 35x = 3 + 0 -4 + 35x = 3 Add '4' to each side of the equation. -4 + 4 + 35x = 3 + 4 Combine like terms: -4 + 4 = 0 0 + 35x = 3 + 4 35x = 3 + 4 Combine like terms: 3 + 4 = 7 35x = 7 Divide each side by '35'. x = 0.2 Simplifying x = 0.2
| 200+1.75x=280.50 | | x^3-2x^2+2=3x^2+5x-23 | | x=4sin(x) | | -2x+5x-2x+3x+1+-2x-3x+4x+3x+5= | | .6x=13.02 | | 3(5a-11)=27 | | 36x^5+24x^3=0 | | 2/3xN=3/8 | | (2b^6)^2/(4b^2)^3 | | (3x-1)(x+2)=-4 | | 2x-7+3x=5x+2-9 | | -4-3(6x+9)=41 | | 8(3+2z)=56 | | 2x9/4 | | abs(3x-8)=5x | | -2/3(-1/5) | | 3x^2-4x+2=x^2+x-6 | | 7n-(4n+16)=7-(3n-2) | | x=0.08-(-0.8) | | 4+10(-2x+3)=-66 | | X=0.08-0.8 | | (x*x)+25x-60=0 | | x+18=6-2x | | -1(-5n)=-7n+3 | | 8x-14+6x-25= | | -1-5n=-7n+3 | | x=2(x^1/2) | | 2.00=(6.00)(8.00)/X | | x=2x^1/2 | | -7x/-1 | | 4.00=(6.00)(8.00)/X | | 5(2x-15)-3x=-124 |